Peran PPAT Dalam Melindungi Hak Kepemilikan Tanah Di Indonesia - Ubaidillah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This research aims to examine the role of Land Deed Officials (PPAT) in protecting land ownership rights in Indonesia. The research method used is qualitative, with a case study approach to gain an in-depth understanding of the role of PPAT. Data was collected through in-depth interviews with PPAT, land owners and other relevant stakeholders. The research results show that PPAT has a key role in protecting land ownership rights by carrying out the process of making legal land deeds and following applicable regulations. However, there are still several challenges such as a lack of public awareness of the importance of PPAT in land transactions and PPAT compliance with professional ethics.